Alterations of neuromuscular function after an ultramarathon - Millet, G. Y.; Lepers, R.; Maffiuletti, N. A.; Babault, N.; Martin, V.; Lattier, G. (Journal of Applied Physiology, 2002)
Neuromuscular fatigue of the knee extensor (KE) and plantar flexor (PF) muscles was characterized after a 65-km ultramarathon race in nine well-trained runners by stimulating the femoral and tibial nerves, respectively. One week before and immediately after the ultramarathon, maximal twitches were elicited from the relaxed KE and PF. Electrically evoked superimposed twitches of the KE were also elicited during maximal voluntary contractions (MVCs) to determine maximal voluntary activation. MVC and maximal voluntary activation decreased significantly after the ultramarathon (30.2 ± 18.0% and 27.7 ± 13.0%, respectively; P < 0.001). Surprisingly, peak twitch increased after the ultramarathon from 15.8 ± 6.3 to 19.7 ± 3.3 N · m for PF (P < 0.01) and from 131.9 ± 21.2 to 157.1 ± 35.9 N for KE (P < 0.05). Also, shorter contraction and half-relaxation times were observed for both muscles. The compound muscle action potentials (M wave) were not significantly altered by the ultramarathon with the exception of the soleus, which showed a slightly higher M-wave amplitude after the running. From these results, it can be concluded that 65 km of running 1) severely depressed the maximal voluntary force capacity mainly because of a decrease in maximal voluntary activation, 2) potentiated the twitch mechanical response, and 3) did not change significantly the M-wave characteristics.